(T)RE(E)MEDIATION - Grusin Richard (Cultural Science)
This essay explores some of the arboreal imaginings that inform analogies between mycorrhizal and technical, or arboreal and human, infrastructural networks. Rather than embrace or dismiss the idea of a wood wide web, I interrogate this intriguing comparison with the help of a variety of natural and human scientists. In so doing I explore how technical, human, arboreal, and mycorrhizal infrastructures are linked by their participation in processes of radical tree mediation.